Mental health and psychological well-being of Kenyan adolescents from Nairobi and the Coast regions in the context of COVID-19 - Mbithi, G; Mabrouk, A; Sarki, A; Odhiambo, R; Namuguzi, M; Dzombo, JT; Atukwatse, J; Kabue, M; Mwangi, P; Abubakar, A (BioMed Central, 2023)
Background Despite the high burden of mental health problems during adolescence and its associated negative consequences, it has remained neglected especially in sub-Saharan Africa. The 2019 novel Coronavirus disease (COVID-19) pandemic has placed additional stress on adolescent mental health. However, there are few studies documenting the burden of mental health problems and even fewer mental health services in the region. In relation to the limited body of knowledge, the present study aims to determine the psychological well-being of adolescents and to assess the risks and associated factors of mental health problems among adolescents in the context of COVID-19 pandemic in Kenya.